Fabrication of dentin-like scaffolds through combined 3D printing and bio-mineralisation. Issue 1 (31st December 2016) - Wu, Yang; Azmi, Danial F.B.; Rosa, Vinicius; Fawzy, Amr S.; Fuh, Jerry Y.H.; Wong, Yoke San; Lu, Wen Feng
Abstract: In this study, polycaprolactone/mineral trioxide aggregate (PCL/MTA) scaffolds were successfully fabricated via an electrohydrodynamic jet (or E-jet) 3D printing system developed by our group. The viscosity of the composited solutions and the key process parameters (i.e. applied voltage and feed rate) were investigated to achieve an optimal process condition. To investigate the potential of PCL/MTA scaffolds to support regeneration ability for dentin related tissue, we seeded dental pulp stem cells on the scaffolds, and compared the results with cell-seeded PCL scaffolds. Assessment of cell viability and proliferation using live/dead cell staining and MTS assay showed compatibility of PCL and PCL/MTA scaffolds for cellular attachment and growth. These scaffolds could be used for fabrication of three-dimensional tissues and in future could be applied to dentin and periodontal tissue engineering applications.